HOW DO GOLD STANDARD FRAMEWORK MEETINGS SUPPORT PALLIATIVE CARE DELIVERY AS PART OF PRIMARY CARE SERVICES? AN OBSERVATIONAL STUDY. Issue Volume 4: Issue (2014)Supplement 1 (1st March 2014) - Haraldsdottir, Erna; Baughan, Paul; Forbat, Liz
Abstract : Background: Whilst uptake of the GSF is widespread there is a lack of evidence to demonstrate how it supports GPs and district nurses to deliver palliative care in primary care. This small study provides insight into the use of GSF meetings within 3 GP practices within NHS Forth Valley. Aim: To identify how GP practices make use of GSF meetings in order to improve palliative care in primary care. Methods: GP practices that were considered as 'good examples', in relation to use of GSF, were invited to take part in the study. 8 GSF meetings were observed and tape recorded. Thematic analysis was used to analyse data, providing order to the data set and allowing for key themes to emerge and be identified. Results: There is ongoing uncertainty amongst GPs related to the criteria for when/what patients should be on the palliative care register, especially for patients with long term condition other than cancer. There was much variation between the GP practices in regards to how many patients they had on the register from 5–54 and this was not in the expected relation to size of practices. GSF meetings were constructed through informal dialogue without any use of formal documents for assessment or management plan. GSF meetings were used for a brief update on the patient condition and situation, key symptom and how they were coping at home. Only one of the three practices used GSF meetings systematically to check if documents related to Advance Care Planning were in place. Conclusion: It appeared that the main benefits of the uptake GSF was related to increased awareness, for those who attended the meeting, of the patients' current situation, possible supporting better coordination of care. However it is unclear how the information sharing benefitted patients in relation to clinical outcomes. Further research is needed to explore how uptake of the GSF improves clinical outcomes.